ANALISIS PENGADAAN BAHAN BAKU BRIKETDALAM MEMENUHI KEBUTUHAN TARGET PRODUKSIPADA UD DEOLEN SEJAHTERA DI KABUPATEN NIAS - Tolona Gea; Maria Magdalena Bate’e; Jeliswan Berkat Iman Jaya Gea; Martha Surya Dinata Mendrofa; Ayler Beniah Ndraha (Jurnal Ilmiah Manajemen Ekonomi Dan Akuntansi (JIMEA), 2024)
The title of this research is entitled "Analysis of Procurement of Briquette Raw Materials to Meet Production Target Needs at UD. Deolen Sejahtera in Nias Regency." This research aims to understand the process of procuring briquette raw materials at UD. Deolen Sejahtera, evaluates the achievement of production targets, identifies obstacles in procuring raw materials, and analyzes the strategies used by the company to achieve production targets. The research method used is a longitudinal approach with a qualitative research type involving 5 informants consisting of 1 owner, 3 employees and 1 supplier. The research results show that UD. Deolen Sejahtera implements a procurement process that involves planning, purchasing, shipping and storing raw materials. Even though the company has extraordinary production targets, the achievement of raw material procurement targets during a certain period is still below 100%. Obstacles in procuring raw materials include price fluctuations, mismatch of purchasing costs with budget, and variations in supplier conditions. Companies adopt strategies such as in-depth understanding of raw material characteristics, clear agreements with suppliers, raw material stock planning, and effective labor monitoring to overcome these challenges. Through this research, it can be useful to provide insight into the importance of effective procurement management in maintaining the smooth production process and achieving company production targets